ELICITING ACTIVITIES MODEL ON STUDENTS' MATHEMATICAL LITERACY ABILITY - Ummu Sholihah; Vera Dewi Susanti (Universitas Muhammadiyah Metro, 2023)
The low level of mathematical literacy in Indonesia is caused by the selection of an inappropriate learning model. The purpose of this study is to review various references related to the eliciting activities model and mathematical literacy. The type of research method used is Systematic Literature Review (SLR). Data collection used library research. A literature study was obtained by searching the sites scopus.com, scimagojr.com, and Google Scholar and grouping the data using publish or perish. From the data obtained, 5 articles were selected from international proceedings and articles from reputable journals. Articles will be reviewed and analyzed with supporting references. The results of this study are known that improving students' mathematical literacy skills depends on the learning model provided and how educators can choose an appropriate learning model and apply the learning model properly. The eliciting activities model can also improve mathematical literacy by modifying learning models with various approaches. In addition, teachers also need to pay attention to each step in the eliciting activities model so that learning objectives can be achieved. Rendahnya literasi matematika di Indonesia diakibatkan pemilihan model pembelajaran yang kurang tepat. Tujuan penelitian ini adalah mengulas berbagai referensi terkait model eliciting activities dan literasi matematika. Jenis metode penelitian yang digunakan yaitu Systematic Literature Review (SLR). Pengumpulan data menggunakan studi pustaka.. Studi pustaka diperoleh dengan  melakukan search proccess  situs scopus.com, scimagojr.com dan google scholar dan  pengempokkan data tersebut menggunakan publish or perish. Data yang sudah diperoleh dipilih 5 artikel dari prosiding internasional dan artikel dari jurnal bereputasi. Artikel akan diulas dan dianalis dengan diperkuat referensi pendukung. Hasil penelitian ini diketahu bahwa peningkatan   kemampuan   literasi   matematika   siswa bergantung dengan  model  pembelajaran  yang  di  berikan dan bagaimana pendidik dapat memilih model pembelajaran yang sesuai dan menerapkan model pembelajaran tersebut dengan baik. Model eliciting activities juga dapat meningkatkan literasi matematika dengan memodifikasi model pembelajaran dengan berbagai pendekatan. Selain itu juga guru perlu memperhatikan setiap langkah pada model eliciting activities agar tujuan pembelajaran dapat tercapai.